PERAN STRATEGIS SERIKAT PEKERJA DALAM MELINDUNGI HAK DAN KESEJAHTERAAN TENAGA KERJA DILINGKUNGAN PERUSAHAAN - Ferdian, Syahrizal Rafli; Firdaus, Latif (SINERGI : Jurnal Riset Ilmiah, 2025)
This research aims to analyze the strategic role of trade unions in efforts to protect the rights and improve the welfare of workers in the corporate environment in Indonesia. Using a descriptive qualitative approach and a comprehensive literature study, this research explores the functions, challenges and effectiveness of trade unions in the context of industrial relations in Indonesia. The results show that trade unions have four main strategic roles: (1) as an instrument of collective bargaining through Collective Labor Agreements (CLAs), (2) as a mechanism for monitoring the implementation of labor regulations, (3) as a channel for advocacy and settlement of industrial disputes, and (4) as a forum for worker empowerment and education. However, the effectiveness of these roles is faced with various challenges such as organizational fragmentation, low membership levels, and resistance from companies. This study recommends strengthening the organizational capacity of trade unions, increasing member participation, and developing sustainable social dialogue to strengthen the role of trade unions in protecting the rights and welfare of workers in Indonesia.